2017
DOI: 10.1073/pnas.1709027114
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a species’ socioecology: Wolves outperform dogs in a conspecific cooperation task

Abstract: A number of domestication hypotheses suggest that dogs have acquired a more tolerant temperament than wolves, promoting cooperative interactions with humans and conspecifics. This selection process has been proposed to resemble the one responsible for our own greater cooperative inclinations in comparison with our closest living relatives. However, the socioecology of wolves and dogs, with the former relying more heavily on cooperative activities, predicts that at least with conspecifics, wolves should coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 54 publications
6
107
5
2
Order By: Relevance
“…Accordingly, wolves seem to excel at tasks that require inhibition in an intraspecific cooperative context (i.e. coordinating and waiting for actions of conspecific partner), which is in line with the predictions derived from the socio-ecological background, while dogs failed to coordinate with each other (Marshall-Pescini et al 2017b). Moreover, it has recently been shown that dogs and wolves differ in their tolerance towards conspecifics (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Accordingly, wolves seem to excel at tasks that require inhibition in an intraspecific cooperative context (i.e. coordinating and waiting for actions of conspecific partner), which is in line with the predictions derived from the socio-ecological background, while dogs failed to coordinate with each other (Marshall-Pescini et al 2017b). Moreover, it has recently been shown that dogs and wolves differ in their tolerance towards conspecifics (e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, also in the other studies where the dogs outperformed wolves in terms of inhibitory control, humans interacted with the animals by constraining them (pointing: Gácsi et al 2009a, b) or repeatedly demonstrating an action (cylinder task: Marshall-Pescini et al 2015). In contrast, when the animals were tested in more asocial settings (detour task: Marshall-Pescini et al 2015;inhibitory control battery: Brucks et al 2019) or where the animal needed to wait for a conspecific partner (Marshall-Pescini et al 2017), wolves did at least as well as if not better than dogs (see also Ostojić and Clayton 2014). However, when comparing the wolves' performance with the performance of the pet dogs in the more asocial delay of gratification task (Brucks et al 2017b), the dogs still outperform the wolves with 5 of the 12 dogs waiting for more than 20 s and as a group, tolerating a mean delay of 35.6 s. Interestingly, the variance of the pet dogs in this self-control task is rather high, and it would be important to know whether the dogs that performed better had some additional training allowing them to tolerate higher delays.…”
Section: Discussionmentioning
confidence: 89%
“…Germar et al 27 , however, examined conformity in dogs, which have a common ancestor with wolves, using the same method as Haun et al 19 , and found that dogs do not copy behaviour presented by multiple conspecific individuals, but stick to what they have learned. Previous studies have also shown that domesticated dogs do not have cooperative behaviour with conspecifics either in a natural environment or under experiment, but wolves do 28,29 . Interestingly, dogs can cooperate with human partners in a string-pulling task as well as wolves can; however, wolves were more likely to initiate movement leading the interaction with humans, whereas dogs were more likely to wait for the human to initiate actions and then follow 30 .…”
Section: Familiarity With Humans Affect Dogs' Tendencies To Follow Humentioning
confidence: 98%